PROFIL ADVERSITY QUOTIENT MAHASISWA FAKULTAS KEDOKTERAN YANG SEDANG MENYELESAIKAN SKRIPSI - Maulina, Bania (Majalah Ilmiah METHODA, 2023)
Previous studies stated that intelligence quotient (IQ) was not able to answer person’s problem of success or failure in their life. In fact, there is another aspect that is just as important, namely adversity quotient (AQ). The current studies showed that AQ was a better index in predicting success. It is not only appear in the world of business and organizations, but also in educational institutions. Every student has expection of graduating on time. In fact, it is not an easy. Many students were found to give up quickly, especially they experienced academic difficulties. The AQ-profile developed by Stoltz was used to obtain AQ profile of 63 students who were completing their thesis. It will be used as a baseline plan related to AQ development. So, the student were able to provide maximum performance. Finally, it was able to increase the percentage of graduation rates on time. Many students showed AQ at a low level, with more quitters than campers and climbers. Based on CO2RE dimensions, origin and ownership indicated the highest category.